Monosaccharides and Ethanol Production from Superfine Ground Sugarcane Bagasse Using Enzyme Cocktail - Jingbo Li; Pengfei Zhou; Hongmei Liu; Jianghai Lin; Yingxue Gong; Wenjuan Xiao; Zehuan Liu (BioResources, 2014)
In this work, the effect of particle size on the enzymatic hydrolysis of milled and sieved sugarcane bagasse (SCB) was studied. The enzymatic hydrolysis and fermentability of superfine ground SCB (SGP400) using an enzyme cocktail strategy were also explored. Particle size reduction improved the enzymatic hydrolysis. The highest glucose yield was 44.75%, which was obtained from SGP400. The enzyme cocktail strategy greatly enhanced the glucose and xylose yield. The maximum glucose and xylose yield was from the enzyme cocktail of cellulase, xylanase, and pectinase. Synergistic action between xylanase and pectinase as well as cellulase and pectinase was quite noticeable. Hydrolysis times affected the degree of synergism. Ethanol production was carried out by employing simultaneous saccharification and fermentation (SSF) and semi-SSF using enzymes and their cocktails. Semi-SSF was found to be the better one compared with SSF. Xylanase and pectinase aided the ethanol production in both fermentation modes. Ethanol yield was 7.81 and 7.30 g/L for semi-SSF and SSF, respectively by using an enzyme cocktail of cellulase, β-glucosidase, pectinase, and xylanase.